Umami Taste for Health - San Gabriel, Ana; Rains, Tia M.; Beauchamp, Gary (Food and Health, 2024)
This Open Access book covers the concept of umami, the unique taste imparted by the amino acid glutamate, was first described in 1908 by Dr. Kikunae Ikeda of Tokyo University. Over the past century, hundreds of studies have explored the mechanistic underpinnings of the taste, leading to the characterization of the umami taste receptor in 2002. How this fifth basic taste figures into nutrition and health, however, remains underexplored. Umami: Taste for Health provides an overview of the relationship between umami and human health. Authors explain how glutamate not only produces a characteristic oral sensation in the mouth but also functions as a signaling molecule to induce physiological responses. With the support of recent studies, the book demonstrates how the taste properties of umami make glutamate a promising substance to lower salt intake, promote satiation and support healthier aging. The text also covers practical culinary applications to increase umami flavor and practical usage of umami for promoting healthy eating. Provides an overview of the relationship between umami and human health; Explores the potential of glutamate to lower salt intake, promote satiation and support healthier aging; Covers practical culinary applications of umami flavor and practical usage of umami for promoting healthy eating.